Shedding light on dark markets: First insights from the new EU-wide OTC derivatives dataset - Jorge Abad; I\~naki Aldasoro; Christoph Aymanns; Marco D'Errico; Linda Rousová; Peter Hoffmann; Sam Langfield; Martin Neychev; Tarik Roukny (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Policy is only as good as the information at the disposal of policymakers. Few moments illustrate this better than the uncertainty before and after the default of Lehman Brothers and the subsequent decision to stand behind AIG. Authorities were forced to make critical policy decisions, despite being uncertain about counterparties' exposures and the protection sold against their default. Opacity has been a defining characteristic of over-the-counter derivatives markets - to the extent that they have been labelled "dark markets" (Duffie, 2012). Motivated by the concern that opacity exercerbates crises, the G20 leaders made a decisive push in 2009 for greater transparency in derivatives markets. In Europe, this initiative was formalised in 2012 in the European Markets Infrastructure Regulation (EMIR), which requires EU entities engaging in derivatives transactions to report them to trade repositories authorised by the European Securities Markets Authority (ESMA). Derivatives markets are thus in the process of becoming one of the most transparent markets for regulators. This paper represents a first analysis of the EU-wide data collected under EMIR. We start by describing the structure of the dataset, drawing comparisons with existing survey-based evidence on derivatives markets. The rest of the paper is divided into three sections, focusing on the three largest derivatives markets (interest rates, foreign exchange and credit).
Keywords: G15; G18; 330; derivatives markets; OTC; financial networks